Kajian Onomastika Teks Perjanjian Baru mengenai Transmisi Nama Diri di dalam Alkitab - Jatmiko, Bakhoh (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2020)
The Bible contains thousands of names in it. Every name presented in the Bible is almost always attached to the message and the meaning behind it. The onomastics biblical study is a linguistic study of the names in the Bible. The method used in this study is a comparative historical linguistic approach to the names in the New Testament text. The study in this article discovers various approaches by the original New Testament authors in reducing personal names in it, namely: transliteration, translation, absorption - Hellenization, giving epithet or cognomen, equivalence, and the usage of nickname or hypocoristic. The findings in this article are useful as references in various discourses related to personal names in the Bible, especially for the Sacred Name Movement group and its variants.